Mapping and systematic appraisal of umbrella reviews in epidemiological research: a protocol for a meta-epidemiological study - Lazaros Belbasis; Robin D Brooker; Emmanuel Zavalis; Angelo Maria Pezzullo; Cathrine Axfors; John PA Ioannidis (Systematic Reviews, 2023)
Abstract Introduction Umbrella review is one of the terms used to describe an overview of systematic reviews. During the last years, a rapid increase in the number of umbrella reviews on epidemiological studies has been observed, but there is no systematic assessment of their methodological and reporting characteristics. Our study aims to fill this gap by performing a systematic mapping of umbrella reviews in epidemiological research. Methods We will perform a meta-epidemiological study including a systematic review in MEDLINE and EMBASE to identify all the umbrella reviews that focused on systematic reviews of epidemiological studies and were published from inception until December 31, 2022. We will consider eligible any research article which was designed as an umbrella review and summarized systematic reviews and meta-analyses of epidemiological studies. From each eligible article, we will extract information about the research topic, the methodological characteristics, and the reporting characteristics. We will examine whether the umbrella reviews assessed the strength of the available evidence and the rigor of the included systematic reviews. We will also examine whether these characteristics change across time. Discussion Our study will systematically appraise the methodological and reporting characteristics of published umbrella reviews in epidemiological literature. The findings of our study can be used to improve the design and conduct of future umbrella reviews, to derive a standardized set of reporting and methodological guidelines for umbrella reviews, and to allow further meta-epidemiological work. Systematic review registration osf.io/sxzc6